Czas jako determinanta elastyczności organizacji - Sus-Januchowska, Aleksandra (The time as a determinant of the flexibility in an organization, 2006)
The growing speed of change is determining work in present organizations. To be on the top means to have the answers and always anticipate changes in the company's corporate culture to allow the free flow of information and feedback. Flexibility is the attribute of the organization which is needed in particular to anticipate the quick changes in today's business environment and to help you stay ahead of your competition. The main factor of flexibility is time. Identifying that part of this factor is the ability to create adaptability and flexibility of the organization is the aim of this article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 53-59